Re-naturalizing the built environment. Plants, architecture, and pedagogy in contemporary green schools - Chiesi, Leonardo; Costa, Paolo; Ciaravella, Fabio; Galmarini, Bianca (Frontiers in Sustainable Cities, 2024)
This study discusses the essential need of re-naturalizing the built environment, focusing on schools. Leveraging research on the impact of nature on health, children's development, and learning, we analyze case studies from America, Asia, and Europe with distinct trajectories of interplay between architecture and pedagogy. Using a theoretical framework on plant-architecture relationship, we identify effective re-naturalization solutions in some applications of biophilic design in rural and urban contexts, cautioning against superficial nature incorporations in schools. Our study asserts that technological sustainability is needed but insufficient, emphasizing the necessity of concurrent efforts in architecture and education to create meaningful student-nature connections.